Penentuan Minimum Inhibitory Concentration (MIC) minyak atsiri Acorus calamus terhadap Aspergillus flavus - Indi Swari, Komang Kartika; Darmayasa, Ida Bagus Gede; Wibawa, I Putu Agus Hendra (Jurnal Biologi Udayana; Vol 28 No 1 (2024): JURNAL BIOLOGI UDAYANA, 2024)
Balinese lontar manuscripts are documentation of past Balinese culture. The main component of palm leaves is cellulose. Efforts to prevent damage to lontar manuscripts from cellulose-degrading fungi such as Aspergillus flavus are needed to maintain Balinese local wisdom. The purpose of this study was to evaluate the Minimum Inhibitory Concentratiton (MIC) value of jangu leaf essential oil ( Acorus calamus ) in inhibiting the growth of A. flavus in vitro. The results obtained were the optimum concentration of A. calamus essential oil at 5% (v/v), with an average inhibition zone diameter of 11.72 mm (strong category). Minimum Inhibitory Concentration (MIC) of jangu leaf essential oil in inhibiting A. flavus is 2% v/v with an average inhibition zone diameter of 7.08 mm. This research opens new insights in the conservation of Balinese ancient manuscripts from damage caused by cellulose-degrading fungi, by utilizing the essential oil of local Balinese plants, namely jangu leaf ( A. calamus ).